Mothers’ non-farm entrepreneurship and child secondary education in rural Ghana - Janssens, Charlotte; Van den Broeck, Goedele; Maertens, Miet; Lambrecht, Isabel B. (International Food Policy Research Institute, 2018)
In this paper we empirically analyse the impact of mothers’ non-farm entrepreneurship on child secondary school enrollment in rural Ghana. We use nationally representative quantitative data from the sixth round of the Ghana Living Standard Survey (GLSS) and qualitative data from focus group discussions throughout rural Ghana. We apply instrumental variable estimation techniques with instruments that pass weak and overidentification tests. We test interaction effects between mothers’ non-farm entrepreneurship and other important determinants of child schooling. We use qualitative data to support our quantitative findings.